2020
DOI: 10.1074/jbc.ra120.015283
|View full text |Cite
|
Sign up to set email alerts
|

An alternative model for type I interferon induction downstream of human TLR2

Abstract: Surface-exposed Toll-like receptors (TLRs) such as TLR2 and TLR4 survey the extracellular environment for pathogens. TLR activation initiates the production of various cytokines and chemokines including type I interferons (IFN-I). Downstream of TLR4, IFNβ secretion is only vigorously triggered in macrophages when the receptor undergoes endocytosis and switches signaling adaptor; surface TLR4 engagement predominantly induces proinflammatory cytokines via the signaling adaptor MyD88. It is unclear if this dichot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 86 publications
2
14
0
Order By: Relevance
“…Indeed, TIRAP silencing led to decreased TNF , IL-6 , IL-1β , IL-12A , and IL-12B mRNA expression following TLR2 and TLR4 stimulation ( Figure S1a,b ). TLR2 did not induce IFNβ mRNA expression or secretion in human MDMs, in agreement with earlier studies [ 29 ]. Notably, in the case of TLR2 and TLR4 stimulation, we have not observed a significant effect on the early induction of pro-inflammatory cytokines ( Figure S1a,b ), which could be due to the still-sufficient amount of residual TIRAP protein for the initiation of signaling, despite a marked decrease in TIRAP-protein expression in silenced MDMs ( Figure S1c ).…”
Section: Resultssupporting
confidence: 93%
“…Indeed, TIRAP silencing led to decreased TNF , IL-6 , IL-1β , IL-12A , and IL-12B mRNA expression following TLR2 and TLR4 stimulation ( Figure S1a,b ). TLR2 did not induce IFNβ mRNA expression or secretion in human MDMs, in agreement with earlier studies [ 29 ]. Notably, in the case of TLR2 and TLR4 stimulation, we have not observed a significant effect on the early induction of pro-inflammatory cytokines ( Figure S1a,b ), which could be due to the still-sufficient amount of residual TIRAP protein for the initiation of signaling, despite a marked decrease in TIRAP-protein expression in silenced MDMs ( Figure S1c ).…”
Section: Resultssupporting
confidence: 93%
“…The detailed signaling pathway of the P3C-IRF axis, the characteristic target of C8keto carotenoids, is still controversial; however, recently, it has been reported that P3C induces IRF activation in THP1-Dual monocytes [39]. Thus, we considered that P3C itself, rather than any possible contaminants, induced IRF activation under our experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, this was not the case, since addition of LPS to the lower compartment in the absence of macrophages, as well as direct stimulation of the apical membrane of the enterocytes with LPS in the presence of PMA-THP-1 cells, did not elicit an inflammatory response (data not shown). The membranes of the two cell lines carry TLR-4 receptors, which recognize LPS and trigger inflammation as well as the increase of gut barrier permeability in human models [19,[39][40][41][42]. However, under our conditions, LPS alone was not able to activate the inflammatory response in Caco-2 cells monolayer.…”
Section: Discussionmentioning
confidence: 62%